Simulation of wind shear - Lim, Desmond Hao Xiang (2015)
Aviation safety has always been a major concern to airliners and safety organisations. Since the 1960s, a weather phenomenon known as microburst has been known to compromise aviation safety. Microburst can create low altitude wind shear which can extend up to 4 km in diameter, and last for up to 15 minutes. In order to better understand the mechanism of wind shear due to microburst as well as generate research data in a bid to improve aviation safety, numerical methods will be used to simulate microburst. LES is an appropriate turbulence model as it provides high fidelity for the large eddies, while modelling the smallest eddies to reduce computation cost and time. The specific solver Jetcode will be used for 6 different simulations; 3 simulations for microburst of varying strength, and 3 simulations for microburst with crosswinds of varying strength. The time history of volume averaged vorticity as well as maximum vorticity in the domain is generated for all 6 simulations. After the initial downdraft impact, microbursts without crosswind displayed a general trend of localised high vorticity regions while microbursts with crosswind displayed vorticity that is spread evenly across the entire domain. A threshold vorticity was determined based on minimum roll rate required by FAR 23 for light aircrafts such as a Cessna 172. Regions of high vorticity were then identified based on this threshold vorticity. Recommendations for improvement are highlighted at the end of the report.